Study on quantitative measurement result of safety culture. (August 2020) - Jiang, Wei; Fu, Gui; Liang, Chun-yang; Han, Wei
Abstract: Based on the quantitative measurement data of safety culture obtained by the research team in the last ten years in China, this paper analyzed the situation of the tested enterprise's safety culture, including 82 enterprises belonging to 17 group companies, involving coal, petroleum, construction, power, shipping, finance, property, chemical industry, equipment manufacturing, non-ferrous metal mine and aviation, a total of eleven categories industries. The surveyed enterprises were mainly concentrated in the coal industry. The staff structure, gender, education level and working years of all employees in 82 enterprises were obtained. Total score of quantitative measurement of safety culture in 82 enterprises and the different employee categories of safety culture quantitative measurement scores were obtained. The overall average level of safety culture of all enterprises tested is 77.4 points, among which the safety culture measurement scores of management, foreman, professional and front-line staff are 78.8, 77.6, 77.4 and 76.7 points respectively. Finally, the gaps and advantages of the safety culture level of all enterprises tested and the safety culture level of other countries' enterprises were determined.